Implementasi Sumber-Sumber Hukum Acara Perdata dan Batas Kewenangan Hakim dalam Sengketa Perdata: Studi Kasus Putusan Nomor 791/Pdt.G/2024/PN Jkt.Utr - Mohammad Ammar Rasya; Rafli Romadhon; Muhammad Aidil Saputra; Mesya Assauma Nurfitrah (Journal of Legal, Political, and Humanistic Inquiry, 2026)
This study examines the implementation of civil procedural law sources and the limitations of judicial authority in civil disputes through a doctrinal legal analysis of Decision Number 791/Pdt.G/2024/PN Jkt.Utr. Employing statute, conceptual, and case approaches, the research analyzes the conformity of procedural norms under the Herziene Indonesisch Reglement, Article 1365 of the Civil Code, and Supreme Court regulations on mediation with the judicial reasoning applied in the case. The findings reveal that procedural law functions not merely as a formal framework but as a normative instrument that guides the admissibility of claims, the assessment of absolute and relative competence, and the proper exercise of judicial authority. Mediation and the principles of simple, swift, and cost-effective justice effectively enhance procedural efficiency while safeguarding the parties’ rights. The study demonstrates that adherence to procedural requirements and the systematic application of civil procedural norms enable courts to maintain legal certainty, uphold jurisdictional limits, and ensure equitable dispute resolution. This research contributes both theoretically and practically to the understanding of procedural law implementation in Indonesian civil courts.